Squamous Cell Carcinoma Arising from Sinonasal Inverted Papilloma - Ginat, D.T. (AJNR Am J Neuroradiol, 2020)
Sinonasal inverted papillomas occasionally undergo malignant transformation into squamous cell carcinoma, which can be associated with EGFR mutations. Since biopsy can potentially under-sample the tumor, CT and MRI can provide clues as to the presence of malignant transformation. In particular, this entity tends to appear different from benign inverted papilloma on imaging, including prominent bone erosions, necrosis, low diffusivity in the solid tumor components, and absence of the cerebriform pattern on MRI. The radiology findings, pathology features, and management of squamous cell carcinoma arising from inverted papilloma are described.